Attitudes and beliefs of immigrants regarding HIV and AIDS in Mopani district, South Africa - Lunic B. Khoza; Hilda N. Shilubane; Mygirl P. Lowane (Taylor & Francis Group, 2020)
Sub-Saharan Africa faces and is severely affected by many conflicts. Human Immunodeficiency Virus (HIV) and Acquired Immunodeficiency Syndrome (AIDS) threaten both the physical and financial well-being of individuals in these struggling countries. This research aims to investigate the immigrants' attitudes and beliefs regarding HIV/AIDS in the Mopani district, Limpopo Province. Qualitative and quantitative designs were used, and 200 immigrants were sampled. Data was collected using a questionnaire with closed and open-ended questions. Ethical standards were maintained. The study revealed that many respondents expressed discriminatory practices towards individuals infected by HIV. Many viewed promiscuity and the disease called Makhume (meaning illness caused by the omission of purification rites following the death of a family member) as causes of HIV/AIDS. These attitudes could hinder the achievement of healthy lives and the promotion of well-being at all ages if not addressed appropriately. The collaboration of various departments in the Mopani district is required to change these negative attitudes and beliefs that influence immigrants' behaviours. Also, the use of audio-visuals and peer teaching is most successful in changing attitudes and beliefs.